Upscaling marine forest restoration: challenges, solutions and recommendations from the Green Gravel Action Group - Wood, Georgina Valentine; Filbee-Dexter, Karen; Coleman, Melinda Ann; Valckenaere, Jurgen; Aguirre, J. David; Bentley, Paige M.; Carnell, Paul; Dawkins, Phoebe Damayanthi; Dykman, Lauren N.; Earp, Hannah S.; Ennis, Leeann B.; Francis, Prue; et al. (Frontiers in Marine Science, 2024)
Introduction To counteract the rapid loss of marine forests globally and meet international commitments of the UN Decade on Ecosystem Restoration and the Convention on Biological Diversity ‘30 by 30’ targets, there is an urgent need to enhance our capacity for macroalgal restoration. The Green Gravel Action Group (GGAG) is a global network of 67 members that are working on the restoration of a diverse range of macroalgal forests and it aims to facilitate knowledge exchange to fast-track innovation and implementation of outplanting approaches worldwide. Methods Here, we overview 25 projects conducted by members of the group that are focused on testing and developing techniques for macroalgal restoration. Based on these projects, we summarise the major challenges associated with scaling up the area of marine forests restored. Results We identify several critical challenges that currently impede more widespread rollout of effective large-scale macroalgal restoration worldwide: 1) funding and capacity limitations, 2) difficulties arising from conditions at restoration sites, 3) technical barriers, and 4) challenges at the restoration-policy interface. Discussion Despite these challenges, there has been substantial progress, with an increasing number of efforts, community engagement and momentum towards scaling up activities in recent years. Drawing on the collective expertise of the GGAG, we outline key recommendations for the scaling up of restoration efforts to match the goals of international commitments. These include the establishment of novel pathways to fund macroalgal restoration activities, building skills and capacity, harnessing emerging innovations in mobile hatchery and seeding technologies, and the development of the scientific and governance frameworks necessary to implement and monitor macroalgal restoration projects at scale.